2010
DOI: 10.1029/2009jd013256
|View full text |Cite
|
Sign up to set email alerts
|

Five year (2004–2009) observations of upper tropospheric water vapor and cloud ice from MLS and comparisons with GEOS‐5 analyses

Abstract: upper tropospheric (UT) water vapor (H 2 O) and ice water content (IWC) from the Aura Microwave Limb Sounder (MLS) and comparisons with outputs from the NASA Goddard Earth Observing System Version 5 (GEOS-5) data assimilation system. Both MLS and GEOS-5 show that high values of H 2 O and IWC at 215 to 147 hPa are associated with areas of deep convection. They exhibit good (within ∼15%) agreement in IWC at these altitudes, but GEOS-5 H 2 O is ∼50% (215 hPa) to ∼30% (147 hPa) larger than MLS values, possibly due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 67 publications
(64 reference statements)
1
37
0
Order By: Relevance
“…Liu (2007) showed in detail that MLS detected ice clouds are geographically and seasonally correlated with deep convection as inferred from the TRMM brightness temperature <210 K. He used MLS IWC at 100 hPa and 147 hPa in particular. Our analysis (Jiang et al, 2007(Jiang et al, , 2010Su et al, 2006) showed 215 hPa IWC correlates with convective intensity. Figure 1 shows the relationship between the MLS IWC measurements at 215 hPa and the GEOS-5 OLR for the tropical region (30 • S to 30 • N).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu (2007) showed in detail that MLS detected ice clouds are geographically and seasonally correlated with deep convection as inferred from the TRMM brightness temperature <210 K. He used MLS IWC at 100 hPa and 147 hPa in particular. Our analysis (Jiang et al, 2007(Jiang et al, , 2010Su et al, 2006) showed 215 hPa IWC correlates with convective intensity. Figure 1 shows the relationship between the MLS IWC measurements at 215 hPa and the GEOS-5 OLR for the tropical region (30 • S to 30 • N).…”
Section: Introductionmentioning
confidence: 99%
“…The GEOS-5 analyses are "snapshots" of the atmospheric state produced four times daily (at 00:00 Z, 06:00 Z, 12:00 Z, and 18:00 Z) using optimal combinations of model forecasts and many observations (Rienecker et al, 2008) via the Gridpoint Statistical Interpolation (GSI) technique of Wu et al (2002). For this study, the GEOS-5 OLR data, which have a 0.5 • × 0.67 • latitude-longitude resolution, are sampled onto the MLS footprints (Jiang et al, 2010) to match the observations. The level of convective detrainment is approximately ∼200 hPa (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…MLS cloud IWC was derived from the 240 GHz cloudinduced radiances at high tangent heights and is scientifically useful at 215-83 hPa (Wu et al, 2008). We include the IWC data in our analysis because it is a proxy for deep convection in the UT (Fu et al, 2006;Jiang et al, 2010Jiang et al, , 2011: larger IWC indicates stronger deep convection. In addition to MLS cloud IWC data, we also examine NOAA outgoing longwave radiation (OLR) interpolated from satellite observations (Liebmann and Smith, 1996).…”
Section: Mls Observations Of Tropical Upper Tropospheric Co and Omentioning
confidence: 99%
“…The control simulation (referred to as CTRL) runs at 50 km horizontal resolution, covering 15 • S to 45 • N and 180 • W to 180 • E. The meridional asymmetry is to avoid a deleterious feedback from a systematic high bias in the Southern Hemispheric (south to 15 • S) TTL water vapor, which appears to be related to poor representation of the stratospheric circulation in this version of WRF (Jiang et al, 2010). A periodic boundary condition is used in the east-west direction.…”
Section: Model Configurationmentioning
confidence: 99%